2020
DOI: 10.3390/ijerph17176042
|View full text |Cite
|
Sign up to set email alerts
|

Family and School Context: Effects on the Mental Health of Brazilian Students

Abstract: Mental health during adolescence can affect an individual’s long-term quality of life. However, the effects of family and school contexts on students’ mental health have been little explored. This study aims to analyze the relationships between family and school life and feelings of loneliness and trouble sleeping owing to worries in adolescents. The data from this cross-sectional study were obtained from Brazil’s National School Health Survey (PeNSE), which obtained its data through questionnaires. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 41 publications
3
33
0
4
Order By: Relevance
“…Our data clearly demonstrated that boys and younger adolescents score higher on the indicators of positive mental health (the life satisfaction and the WHO-5 scale) and lower on the indicators on negative mental health (the symptoms checklist and the MHI-5). That boys and younger adolescents report better mental health has been widely reported previously internationally [ 41 , 42 , 43 ] and in Ireland [ 38 , 44 , 45 ], and the current findings support this. We also found that the decrease in reported positive mental health and increase in reported mental health problems in girls as they get older is more pronounced than that of boys, as was previously reported in Ireland [ 38 , 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our data clearly demonstrated that boys and younger adolescents score higher on the indicators of positive mental health (the life satisfaction and the WHO-5 scale) and lower on the indicators on negative mental health (the symptoms checklist and the MHI-5). That boys and younger adolescents report better mental health has been widely reported previously internationally [ 41 , 42 , 43 ] and in Ireland [ 38 , 44 , 45 ], and the current findings support this. We also found that the decrease in reported positive mental health and increase in reported mental health problems in girls as they get older is more pronounced than that of boys, as was previously reported in Ireland [ 38 , 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…The research found that the use of social distancing and stay-at-home orders to mitigate the spread of COVID-19 is negatively affecting the mental health of young people as has been seen elsewhere [8]. There is an increased risk of developing psychiatric disorders, such as depression and anxiety during these formable years with half of all mental health disordered developing before the age of 14 [15]. For adolescents, this risk is complicated by how hormonal and neurobiological changes correspond to increased emotional reactivity and continual development of stress regulation and coping strategies [38].…”
Section: Social Isolationmentioning
confidence: 97%
“…Some groups may be more vulnerable to the psychosocial effects of the COVID-19 pandemic than others. Because they are in a critical period of development, with half of all mental health disordered developing before the age of 14 [15], children and adolescents must be provided with adequate supports. Factors associated with mitigation measures such as social distancing, family discord, school closures, fears about the future, and quarantine are disrupting young people's lives [4,16].…”
Section: The Psychological Impact Of Covid-19 On Children and Adolescmentioning
confidence: 99%
See 1 more Smart Citation
“…In the prevention of mental health, it is also relevant to consider the context in which the person develops. The study of Escobar et al [ 17 ] indicated that mental health issues were associated with hunger, distant relationships with parents, and family violence within the family context. In addition, the relationship between adolescents with a poorer family context and subjective wellbeing is well established [ 18 ].…”
mentioning
confidence: 99%